2021
DOI: 10.1177/17442591211009937
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis of the hygrothermal behaviour of homogeneous masonry constructions: Interior insulation, rainwater infiltration and hydrophobic treatment

Abstract: Historical masonry constructions are difficult to mimic in hygrothermal models. The material properties of the walls are often highly uncertain due to the natural origin of the aggregates and the various, manual production processes used through time. Therefore, sensitivity analyses based on probabilistic simulations are powerful tools to indicate the risks on damage in masonry constructions. Damage criteria for relevant pathologies such as frost damage, potential decay of wooden beam heads and mould growth at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Gutland et al (2021) proposed a methodology to model the cracks as separate material thus accounting for both accelerated wetting and drying through the imperfections. In Calle et al (2020Calle et al ( , 2021 the wall with imperfections resulted in being wetter, while in Gutland et al (2021) drier in long-term than regular baseline model. However, the latter method would benefit from experimental validation and requires simplification to make it applicable to large modelling campaigns.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Gutland et al (2021) proposed a methodology to model the cracks as separate material thus accounting for both accelerated wetting and drying through the imperfections. In Calle et al (2020Calle et al ( , 2021 the wall with imperfections resulted in being wetter, while in Gutland et al (2021) drier in long-term than regular baseline model. However, the latter method would benefit from experimental validation and requires simplification to make it applicable to large modelling campaigns.…”
Section: Resultsmentioning
confidence: 92%
“…An aspect not dealt with in detail in this study is imperfections of masonry – while the influence of contact resistances is explored, the additional water infiltration due to cracking is not. Based on experiments, Calle et al (2020) and Calle & Van Den Bossche (2021) suggested leakage rates to be applied as sources inside the wall. Gutland et al (2021) proposed a methodology to model the cracks as separate material thus accounting for both accelerated wetting and drying through the imperfections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the material should be at a critical degree of saturation of moisture content at the time of freezing, and the internal freezing stresses should be higher than the material strength [54,55]. The accurate representation of these mechanisms and direct conclusions on freeze-thaw damage would require a hygrothermal simulation, eventually coupled to a mechanical simulation, which could resolve the occurrence of freezing and thawing locally, considering the pore-size distribution of the material [12,56,57] and the resulting mechanical stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in a second part the scope was extended and the relation between the response behavior and physical properties was assessed based on various sensitivity analyses. This included scatterplots, binary Poison distribution-based classification trees as well as Spearman rank correlations (Calle, 2020; Calle and Van Den Bossche, 2021; Hagentoft, 2017; Hamby, 1994). Three empirical degradation models were adopted and because of their inherent differences in nature, the results were first analyzed separately.…”
Section: Methodsmentioning
confidence: 99%